Characterization of 13.56 MHz RF Ne-N2 mixture plasma using intrusive and non-intrusive diagnostic techniques - Rehman, N.U. (2013)
RF generated Ne-N2 mixture plasmas are investigated to evaluate the variation in electron temperature (Te) and vibrational temperature (TÎ½) of the ground state N2 (X,Î½ ), the second positive system and the first negative system of nitrogen; the electron energy probability function and the population densities of the reactive atomic, molecular and ionic species of nitrogen; and the rotational temperature (T rot) of the first negative system of nitrogen, as a function of discharge parameters. Optical emission spectroscopy and a Langmuir probe are employed to characterize the plasmas. It is observed that the density of reactive species and Te, as well as TÎ½ (the second positive and first negative system), increase with RF power and neon percentage in the mixture. However, Te decreases with total pressure while TÎ½ (the second positive and first negative system) increases up to a pressure of 0.5 mbar. The vibrational temperature of the N2 (X,Î½ ) state has been measured indirectly through the N2 (C 3Î u ) state distribution, and it is noted that it increases up to 60 neon in the mixture and then decreases. On the other hand, the density of the reactive species corresponding to atomic nitrogen increases with increase in neon percentage, and after reaching an optimum value, starts to decrease. The rotational temperature of the first negative system of nitrogen has been measured using the Boltzmann plot method and it is observed that it increases gradually up to 60 neon in the mixture and then falls slightly at 0.5 mbar pressure. Â© 2013 The Royal Swedish Academy of Sciences.